2016
DOI: 10.1038/srep22838
|View full text |Cite
|
Sign up to set email alerts
|

Independent control of electrical and heat conduction by nanostructure designing for Si-based thermoelectric materials

Abstract: The high electrical and drastically-low thermal conductivities, a vital goal for high performance thermoelectric (TE) materials, are achieved in Si-based nanoarchitecture composed of Si channel layers and epitaxial Ge nanodots (NDs) with ultrahigh areal density (~1012 cm−2). In this nanoarchitecture, the ultrasmall NDs and Si channel layers play roles of phonon scattering sources and electrical conduction channels, respectively. Electron conductivity in n-type nanoacrhitecture shows high values comparable to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…The Si layer and the Ge NDs should serve as the electrical conduction layer and phonon scattering bodies, respectively. Because the separate structures have separate roles, we expected independent control of the electrical and thermal conductivities [ 31 ]. The density of the ND interfaces and their size were correlated within the structure of the connected Si NDs.…”
Section: Strategy For Thermal and Electrical Control Using Nanostructmentioning
confidence: 99%
“…The Si layer and the Ge NDs should serve as the electrical conduction layer and phonon scattering bodies, respectively. Because the separate structures have separate roles, we expected independent control of the electrical and thermal conductivities [ 31 ]. The density of the ND interfaces and their size were correlated within the structure of the connected Si NDs.…”
Section: Strategy For Thermal and Electrical Control Using Nanostructmentioning
confidence: 99%
“…In this structure, epitaxial Ge NDs worked as phonon scattering centers and epitaxial Si layers worked as electric conduction layers. This result indicated the possibility of the independent control of the thermal and electric conductivities [2,3]. However, S was not controlled in this nanostructure.…”
Section: Introductionmentioning
confidence: 78%
“…To cite this article: S. Sakane CREST-JST, Japan, 3 Tohoku University, Japan, 4 Shiga university of Medical Science, Japan *E-mail: nakamura@ee.es.osaka-u.ac.jp Abstract. Nanostructures are expected to enhance thermoelectric properties of Si-based materials.…”
Section: Formation Of Various Epitaxial Nanodots In Si Films For Thermentioning
confidence: 99%
“…In fact, thermal conductivity can be significantly reduced owing to nanostructured materials. 37 Recently, the interest in thermoelectric devices has gained momentum with the advances in nanostructural engineering, which led to overall efforts to demonstrate high-efficiency materials. At the same time, complex bulk materials (such as skutterudites, clathrates, and Zintl phases) have been explored, and it was found that highefficiencies could be obtained.…”
Section: Thermoelectric Device: From Bulk To Nanomentioning
confidence: 99%